Lessons Learned from an Operational Smart Grid Through the Example of a Local Government in Hungary - Piricz, Noémi; Révész, Balázs (Public Finance Quarterly, 2022)
The steadily growing global demand for electricity, sustainability expectations, the global Covid epidemic and the Russian-Ukrainian war are also affecting the electricity supply chain. In our study we will focus on the smart grid, the modern smart electricity network of the near future, from a Hungarian perspective, with management approach. Hungary’s newest and most complex smart grid is analysed using the case study method. We investigated the actors of the smart grid and were interested in how the cooperation between the parties was, what learning processes they experienced, and what risks they saw and see now. Our results show that customers and contractors are mutually satisfied; in addition to the numerical benefits, each party also values the learning processes in different areas. The risks identified stem from modern technology, complexity, novel solutions and operational mechanisms, but geopolitical, global economic uncertainties and shortages also have an impact.